The musicians of Bremen - Southgate, Vera (USA : Ladybird Books, 1990)
No longer wanted by their masters, a donkey, dog, cat, and rooster set out for Bremen to become musicians
Primary
Keywords: Children's stories in English, 1945 -- Texts; Folklore -- Germany; Animals -- Juvenile fiction; Music -- Juvenile fiction